2007
DOI: 10.1021/om700864u
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Molybdenum Imido Alkylidene Complexes That Contain Siloxides

Abstract: Monosiloxide and disiloxide complexes have been prepared through the addition of silanols to Mo(NR)(CHCMe 2 Ph)(pyrrolyl) 2 species [R ) 1-adamantyl (Ad) or 2,6-i-Pr 2 C 6 H 3 (Ar)]. The silanols employed include (t-Bu) 3 SiOH (HSilox), (i-Pr) 3 SiOH, (Me 3 Si) 3 SiOH, (t-Bu-O) 3 SiOH, Me 2 (t-Bu)SiOH, and Ph 3 SiOH. The monoSilox complex, Mo(NAr)(CHCMe 2 Ph)(Silox)(pyrrolyl) (2a), could be isolated, while Mo(NAd)(CHCMe 2 Ph)(Silox)(pyrrolyl) was observed in situ but could not be crystallized. Disiloxides that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 27 publications
(27 reference statements)
1
20
0
Order By: Relevance
“…In contrast, using Surface Organometallic Chemistry, [3][4][5][6] a large family of highly active supported alkene metathesis catalysts has been reported based on welldefined metal alkylidenes in the past 15 years. [7][8][9][10][11][12][13][14][15] These numerous complexes have given access to a large number of spectroscopic and catalytic data set that have contributed to a better understanding of the mechanism and reaction intermediates involved in alkene metathesis. 10,12,14 In an attempt to bridge the gap between these and classical illdefined WO 3 /SiO 2 catalysts, 1,2,16 we have recently investigated the synthesis of silica supported oxo alkylidene complexes, which present very high activity ( Figure 1b).…”
Section: Supporting Information Placeholdermentioning
confidence: 99%
“…In contrast, using Surface Organometallic Chemistry, [3][4][5][6] a large family of highly active supported alkene metathesis catalysts has been reported based on welldefined metal alkylidenes in the past 15 years. [7][8][9][10][11][12][13][14][15] These numerous complexes have given access to a large number of spectroscopic and catalytic data set that have contributed to a better understanding of the mechanism and reaction intermediates involved in alkene metathesis. 10,12,14 In an attempt to bridge the gap between these and classical illdefined WO 3 /SiO 2 catalysts, 1,2,16 we have recently investigated the synthesis of silica supported oxo alkylidene complexes, which present very high activity ( Figure 1b).…”
Section: Supporting Information Placeholdermentioning
confidence: 99%
“…For example, it has been shown that ligands can be so sterically demanding that a 14e species simply does not react readily even with ethylene. A rare example of this type is Mo(NAdamantyl)(CHCMe 2 Ph)(Silox) 2 (Silox = OSi(t-Bu) 3 ), which is unchanged after being heated in toluene-d 8 under five atm of ethylene at 120 °C for several hours, in contrast to facile reactions of many other siloxide, aryloxide, or alkoxide derivatives xix. However, Mo(NAd)(CHCMe 2 Ph)(pyrrolide)(Silox) ( vide infra ) does react with ethylene and terminal olefins.…”
Section: Principles Of Tungsten and Molybdenum Imido Alkylidene Chmentioning
confidence: 99%
“…50 % intact after four weeks). Other prototype molybdenum alkylidenes such as the triphenylsilanolate complex 4 [11] and the chiral variant 6 [12] also form adducts that remain intact when stored without any precautions for extended periods (Scheme 1).The structure of the particularly robust complex 3 in the solid state is depicted in Figure 1. The coordination geometry about the Mo VI center can be described as distorted octahedral, with the imido ligand and one of the two inequivalent hexafluoro-tert-butanolates residing trans to each other, even though the corresponding N3-Mo1-O2 angle (167.04(4)8) strongly deviates from linearity.…”
mentioning
confidence: 99%